AN UPDATE OF CLINICAL TRIALS LANDSCAPE IN TÜRKİYE - Ayşegül Özsoy; Selçuk Şen (Sabiad)
Objective: Clinical research is essential to enhance scientific knowledge and provide better patient outcomes. This work evaluated clinical trials in Türkiye between 2019-2023 and compared them with previous research.Material and Method: Clinical trials in Türkiye registered in the ClinicalTrials.gov database between 01.01.2019 and 30.09.2023 were examined and evaluated. Trials were filtered by study type, study phase, recruitment status, funder type, location, condition, or disease. Comparative analyses were executed for different cities and countries.Results: The total number of registered clinical trials in Türkiye was 12,563. The number of trials registered between 2019 and 2023 was 8,851. Of these, 68.21% were interventional and 9.3% were industrysponsored. The majority of trials (61.13%) were completed, while 18.78% were still recruiting patients. Leading cities in Türkiye were Istanbul and Ankara with the highest trial numbers. Despite a remarkable increase in the total number of clinical trials in Türkiye, no considerable change was detected in the number of industry-sponsored trials. The majority of trials with unknown status (85%) were non-industry-sponsored in all countries in the comparative analysis. The highest numbers of trials were found in respiratory, pain/pain management and oncology in Türkiye among the evaluated fields including cardiovascular disease, genetic disorders, diabetes, and obesity.Conclusion: The total number of clinical trials in Türkiye showed a considerable increase when compared with developed countries including Germany, France, and the United Kingdom, however, the reasons behind the lower number and stability in the yearly increase rate of industrysponsored trials should be revisited by all stakeholders.